Optimization of Kamsel Unit Performance Through Dikmas Activities for Students to Prevent Traffic Violations in the Jurisdiction Area of Pemalang - Simarmata, Afif Togu Arfenta (Advances in Police Science Research Journal, 2024)
For the purpose of conducting this research, it is to describe the performance of the Kamsel Polres Pemalang unit in preventing traffic violations that occur among students by carrying out direct community education to students in the jurisdiction of Pemalang so that awareness and knowledge arises about the importance of not carrying out traffic violations. In carrying out this final assignment, the authors used several concepts and theories which were used as analytical tools, namely the concept of optimization, the concept of direct community education, the concept of traffic violations, management theory, SWOT theory and the approach used in this study, namely a qualitative approach, to data collection techniques using interview techniques, observation, document study From the results of the research that has been carried out, the author finds that the performance carried out by the Kamsel unit still has deficiencies in the context of preventing traffic violations, especially among students because the students’ own knowledge of traffic rules is still minimal. So it can be concluded that in terms of performance there is still a need for improvement carried out by members of the Kamsel Unit.